Diagnosing Mental Models of Undergraduate Student and Physics Teachers: Study Case in the Momentum and Energy Conservation Principles Using Newton's Cradle - Sarapak, C.; Kearns, K. (Jurnal Pendidikan IPA Indonesia, 2022)
The Newton’s Cradle comprises a series of pendulums often used in physics classrooms to demonstrate the principles of conservation of momentum and kinetic energy in elastic collisions. By utilizing open-ended questions and several Newton’s cradle scenarios, this study aims to clarify how the Newton’s cradle can be used for assessing the mental models of the principles of conservation of momentum and energy. Interviews with 18 college students and five physics professors each lasted 30 to 45 minutes. Firstly, they were asked to explain how the Newton’s cradle works. Next, a scenario started with three balls with equal masses where one collides with the other two, they were asked to explain if the possible outcomes for a collision with initial momentum = mv1 + 0 + 0 and the final momentum = (-mv1/3) + (2mv1/3) + (2mv1/3). With a five-ball Newton’s Cradle, students were asked to explain the outcomes when 1) one collides with the other four, 2) two collide with the other three, 3) three collide with the other two, and 4) four collide with the last one. Their drawings and explanations dealing with the Newton’s cradle during the interviews were analyzed for their mental models and categorized into patterns. The results showed that both university students and physics teachers hold misinformed conceptions about conservation of momentum and energy and have unsound mental models in the context of Newton’s Cradle. We also found that they did not recognize that sound and heat or lack of exact alignment of the balls are factors accountable for loss of energy causing the Newton’s Cradle to depart from idealized situation. Based on the interview data, teaching principles of the conservation of momentum and energy through use of Newton’s cradle are deficient and curriculum review is suggested.